Peptide-Based Materials - Deming, Timothy; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
Synthesis of Polypeptides by Ring-Opening Polymerization of ga(B-Amino Acid N-Carboxyanhydrides, by Jianjun Cheng and Timothy J. Deming.- Peptide Synthesis and Self-Assembly, by S. Maude, L. R. Tai, R. P. W. Davies, B. Liu, S. A. Harris, P. J. Kocienski and A. Aggeli.- Elastomeric Polypeptides, by Mark B. van Eldijk, Christopher L. McGann, Kristi L. Kiick andJan C. M. van Hest.- Self-Assembled Polypeptide and Polypeptide Hybrid Vesicles: From Synthesis to Application, by Uh-Joo Choe, Victor Z. Sun, James-Kevin Y. Tan and Daniel T. Kamei.- Peptide-Based and Polypeptide-Based Hydrogels for Drug Delivery and Tissue Engineering, by Aysegul Altunbas and Darrin J. Pochan.-s
Synthesis of Polypeptides by Ring-Opening Polymerization of ga(B-Amino Acid N-Carboxyanhydrides, by Jianjun Cheng and Timothy J. Deming -- Peptide Synthesis and Self-Assembly, by S. Maude, L. R. Tai, R. P. W. Davies, B. Liu, S. A. Harris, P. J. Kocienski and A. Aggeli -- Elastomeric Polypeptides, by Mark B. van Eldijk, Christopher L. McGann, Kristi L. Kiick andJan C. M. van Hest -- Self-Assembled Polypeptide and Polypeptide Hybrid Vesicles: From Synthesis to Application, by Uh-Joo Choe, Victor Z. Sun, James-Kevin Y. Tan and Daniel T. Kamei -- Peptide-Based and Polypeptide-Based Hydrogels for Drug Delivery and Tissue Engineering, by Aysegul Altunbas and Darrin J. Pochan.-.s
Keywords: Chemistry; Polymers; Biochemistry; Biomaterials; Chemistry; Polymer Sciences; Biomaterials; Biochemistry, general